Kajian Ekstensifikasi Barang Kena Cukai pada Minuman Ringan Berkarbonasi - CHANDRA, ESTHER MARIA; GUFRAENI, RINI (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
The Indonesian government has attempted to increase the function of excise duty as the source of revenue and consumer goods controller by expanding excise-taxed goods on carbonated soft drinks. This research aimed to learn the background, the government’s effort, and the revenue potential of carbonated soft drinks. The result showed that the expanding of the goods are based on their nature and characteristics of excise-taxed goods—regulated in Law No. 39 of 2007 as goods whose consumption must be limited, whose distribution must be controlled, and whose usage produces a negative impact on the health of the people and the environment; as well as goods whose usage is taxed for the sake of justice. The efforts done by the government are to revise the Excise Law, to conduct a deep study and internal socialization, and to establish accountable human resources. It is hoped that eventually the implementation of excise duty on carbonated soft drinks would increase state revenue without at the same time neglecting programs of people’s health improvement.